3-MA Inhibits Autophagy and Favors Long-Term Integration of Grafted Gad67–GFP GABAergic Precursors in the Developing Neocortex by Preventing Apoptosis. Issue 11 (November 2014) - Roux, Christian; Lesueur, Céline; Aligny, Caroline; Brasse-Lagnel, Carole; Genty, Damien; Marret, Stéphane; Laquerrière, Annie; Bekri, Soumeya; Gonzalez, Bruno J.
In human neonates, immature GABAergic interneurons are markedly affected by an excitotoxic insult. While in adults the interest of cell transplantation has been demonstrated in several neurological disorders, few data are available regarding the immature brain. The low survival rate constitutes a strong limitation in the capacity of transplanted neurons to integrate the host tissue. Because i) autophagy is an adaptive process to energetic/nutrient deprivation essential for cell survival and ii) literature describes cross-talks between autophagy and apoptosis, we hypothesized that regulation of autophagy would represent an original strategy to favor long-term survival of GABAergic precursors grafted in the immature neocortex. Morphological, neurochemical, and functional data showed that in control conditions, few grafted Gad67-GFP precursors survived. The first hours following transplantation were a critical period with intense apoptosis. Experiments performed on E15.5 ganglionic eminences revealed that Gad67-GFP precursors were highly sensitive to autophagy. Rapamycin and 3-MA impacted on LC3 cleavage, LC3II translocation, and autophagosome formation. Quantification of Bax, mitochondrial integrity, caspase-3 cleavage, and caspase-3 immunolocalization and activity showed that 3-MA induced a significant decrease of Gad67-GFP precursor apoptosis. In vivo, 3-MA induced, within the first 24 h, a diffuse LC3 pattern of grafted Gad67-GFP precursors, an increase of precursors with neurites, a reduction of the density of caspase-3 immunoreactive cells. A twofold increase in the survival rate occurred 15 days after the graft. Surviving neurons were localized in the cortical layers II–IV, which were still immature when the transplantation was done. Altogether, these data indicate that inhibition of autophagy represents an original strategy to allow GABAergic interneurons to overpass the first critical hours following transplantation and to increase their long-term survival in mice neonates.